Servidores de correo y listas de correo - Kelleghan Monge, James Patrick (My University, 1998)
The sendmail (1M) program implements a general-purpose internetwork mail routing facility under the UNIX operating system. It features aliasing, forwarding, automatic routing to network Gateways, and flexible, and flexible configuration features. The sendmail program came into being because mailing through heterogeneous.
Keywords: administration; sendmail; debugging; command; DFS